2020
DOI: 10.1097/md.0000000000020235
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study to explore the correlation of peripheral arterial pulse/resistance index, organ function, and inflammation in patients with septic shock

Abstract: Introduction: The evaluation of the functional status of blood vessels, especially the arterial system, plays a very important role in the judgment of the condition of septic shock patients and the guidance of resuscitation programs and the judgment of the therapeutic effect. We aimed to design an observational study protocol to explore the correlation of peripheral arterial pulse/resistance index, organ function and inflammation in patients with septic shock. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…This finding confirms the effectiveness of UTI in controlling infections and suppressing inflammatory responses with good efficacy, including endotoxin, which is consistent with previous studies on UTI efficacy in treating pulmonary, urinary, and post‐traumatic infections 30,31 . Patients in the study group showed subjective improvement in inflammation control, as indicated by a reduction in the ICU stay, duration of fever, and maintenance of vasoactive drugs, when compared to the control group, by 16−24 h. This result is consistent with the findings reported by Hu et al 44 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding confirms the effectiveness of UTI in controlling infections and suppressing inflammatory responses with good efficacy, including endotoxin, which is consistent with previous studies on UTI efficacy in treating pulmonary, urinary, and post‐traumatic infections 30,31 . Patients in the study group showed subjective improvement in inflammation control, as indicated by a reduction in the ICU stay, duration of fever, and maintenance of vasoactive drugs, when compared to the control group, by 16−24 h. This result is consistent with the findings reported by Hu et al 44 …”
Section: Discussionsupporting
confidence: 91%
“…This finding confirms the effectiveness of UTI in controlling infections and suppressing inflammatory responses with good efficacy, including endotoxin, which is consistent with previous studies on UTI efficacy in treating pulmonary, urinary, and post-traumatic infections. 30,31 Patients in the study group showed subjective improvement in inflammation control, as indicated by a reduction in the ICU stay, duration of fever, and maintenance of vasoactive drugs, when compared to the control group, by 16−24 h. This result is consistent with the findings reported by Hu et al 44 The liver of patients with an unliquefied bacterial LA, combined with infectious shock, is one of the more heavily involved target organs in these patients, and the production of large amounts of inflammatory mediators in the body during SIRS easily induces apoptosis of hepatocytes, which together with tissue ischemia-reperfusion injury and microthrombus formation, can easily lead to acute liver injury and even liver failure. 7,15,17,18 Changes in indices, such as TBil, ALT, and AST, reflect the severity of damage to liver function, and some studies have linked hyperbilirubinemia to eventual death from PLA.…”
Section: Clinical Informationsupporting
confidence: 89%
“…The pathogenic microorganisms in the infected lesions and the endotoxins and exotoxins released can activate complement and stimulate neutrophils and macrophages to release a large amount of IL-6, TNF- α , and other inflammatory factors which participate in the inflammatory response [ 17 , 18 ]. PCT in the human body is at a very low level under normal circumstances, and it will increase significantly when the body has a serious infection or sepsis, which is an important indicator for observing the infection of the body [ 19 ].…”
Section: Discussionmentioning
confidence: 99%